Revitalization of Tolerance Values through The Saparan Tradition: A Study in Pondok Wonolelo Village - Sa'adah, Afifah Nurul; Sudrajat, Sudrajat (UIN Maulana Malik Ibrahim Malang, 2023)
The Saparan tradition is carried out every Safar month and is followed by village communities with differences. This research aims to determine the values of tolerance in the Saparan Tradition in Pondok Wonolelo Hamlet, Widodomartani, Ngemplak, Sleman. The type of research used by researchers is naturalistic qualitative. Data collection used was observation, interviews, and documentation. The results of the study show that the forms of tolerance values in the Saparan Tradition in Pondok Wonolelo Hamlet are 1) attitudes of mutual respect and respect for other people and cooperation are found in recitation activities, heritage parades, bregodo parades, distribution of apem and supporting events, 2) attitudes not discriminating/discriminating and not hurting/interfering with other people's freedom is found in the heritage carnival, bregodo carnival, apem distribution, and supporting events, and 3) caring for each other is found in the heirloom carnival, bregodo carnival, and supporting events. However, during the heirloom carnival and bregodo activities during traditional ceremonies, the implementation of the event still differentiates in its reception between poor and rich people. Apart from that, there is still a lack of concern during recitations, heritage carnivals and bregodo for the elderly/disabled. In short, the Saparan Tradition can bring values of tolerance to the people of Pondok Wonolelo Hamlet. However, in practice, the community is still not tolerant of some Saparan Tradition activities. This research recommends the importance of mutual tolerance between members of society. Tradisi Saparan dilaksanakan pada setiap bulan Safar yang diikuti oleh masyarakat desa dengan beragamnya perbedaan. Penelitian ini bertujuan untuk mengetahui nilai-nilai toleransi pada Tradisi Saparan di Dusun Pondok Wonolelo, Widodomartani, Ngemplak, Sleman. Jenis penelitian yang digunakan peneliti adalah kualitatif naturalistik. Pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa bentuk nilai-nilai toleransi pada Tradisi Saparan di Dusun Pondok Wonolelo, yaitu 1) sikap saling menghargai dan menghormati orang lain serta gotong royong terdapat pada kegiatan pengajian, kirab pusaka, kirab bregodo, penyebaran apem dan acara penunjang, 2) sikap tidak mendiskriminasi/membeda-bedakan dan tidak menyakiti/mengganggu kebebasan orang lain terdapat pada kirab pusaka, kirab bregodo, penyebaran apem dan acara penunjang, dan 3) saling peduli terdapat pada kegiatan kirab pusaka, kirab bregodo dan acara penunjang. Namun, pada kegiatan kirab pusaka dan bregodo saat upacara adat dalam pelaksanaan acara masih membeda-bedakan dalam penyambutannya antara masyarakat yang miskin dan kaya. Selain itu, masih terdapat sikap kurang peduli saat pengajian, kirab pusaka dan bregodo pada lansia/difabel. Secara singkat, Tradisi Saparan dapat menghadirkan nilai-nilai toleransi pada masyarakat Dusun Pondok Wonolelo, namun dalam pelaksanaannya masyarakat masih tidak bersifat toleran dalam beberapa kegiatan Tradisi Saparan. Penelitian ini merekomendasikan pentingnya saling toleransi antar anggota masyarakat.